SAS companion for P.V. Rao's Statistical research methods in the life sciences - Younger, Mary Sue
Available for bundling with Rao's text, this unique companion shows in great detail how to use SAS to do the statistics described in the text. Written specifically to complement and enhance the SAS material in the book, the SAS Companion uses the same examples used in the text, providing instructions and output for all textual examples. The SAS Companion is an essential tool and a handy reference for students as they work through the books' computing assignments